Economic freedom and Hofstede's cultural dimensions. Issue 1 (18th December 2019) - DeBode, Jason D.; Haggard, Dana L.; Haggard, K. Stephen
Abstract : Purpose: The purpose of this paper is to investigate the influence of broad cultural dimensions, as well as those of religion and legal origin, on countries' economic freedom, i.e., trade freedom, investment freedom, business freedom, labor freedom, monetary freedom, as well as a composite measure of economic freedom. Design/methodology/approach: Linear regression of publicly available data regarding economic freedom (Miller et al., 2018 ) on cultural dimensions (Hofstede, 2009), legal origin and religion (LaPorta et al., 1999 ) for 52 countries was performed to determine the impact of these factors on economic freedom. Findings: Results indicated femininity was the cultural dimension associated with the most measures of economic freedom. Short-term-oriented cultures were predictive of greater business freedom, while more restrained cultures were associated with greater business and monetary freedoms. Higher individualism was predictive of greater monetary freedom. Catholicism positively predicted investment freedom and negatively predicted business freedom. French civil law negatively predicted labor freedom, while socialist legal origins positively predicted trade freedom, but negatively predicted business freedom. Originality/value: This is the first study to examine the impacts of culture, law and religion on economic freedom. One practical implication of this research is that countries would be wise to emphasize more feminine aspects in their cultures, as these are associated with greater economic freedom. Even minor adjustments that move in the direction of cooperation and fair processes might help increase economic freedoms and the many benefits that stem from such freedoms.